2020
DOI: 10.1177/0333102420977852
|View full text |Cite
|
Sign up to set email alerts
|

Identification of work accommodations and interventions associated with work productivity in adults with migraine: A scoping review

Abstract: Objective To identify factors associated with work productivity in adults with migraine, and accommodations or interventions to improve productivity or the workplace environment for them. Methods We conducted a scoping review by searching MEDLINE, Embase, PsycINFO, Cumulative Index of Nursing and Allied Heath Literature, and Web of Science from their inception to 14 October 2019 for studies of any design that assessed workplace productivity in adults with migraine. Results We included 26 articles describing 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…Despite the impact of headache on output, it has been observed that there is a lack of reliable data on headache-related work factors associated with productivity [ 73 ]. This study aims to reduce this information gap.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the impact of headache on output, it has been observed that there is a lack of reliable data on headache-related work factors associated with productivity [ 73 ]. This study aims to reduce this information gap.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples are workplace accommodations to increase productivity in workers with migraine (73). Therapy delivered to groups of people with headache (focused on education, non-pharmacological treatment, psychotherapy, and self-management) show promise and may be more effective than individual delivery (7477). There may, however, be negative effects of improving support, such as pain avoidance, over-dependence on others, and reinforcement of anxieties (78).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, failing to properly recognize actual risk factors would result in inaccurate management, and higher relapse rates. In this regard, the relatively low share of participants identifying main risk factors such as working rhythms and working hours as potential barriers to a proper management of migraine may be particularly frightening [ 34 , 35 , 36 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%